The Use of Scanning IT Tools in the Analysis of Tendencies to Take Risk - Radoslaw MILEWSKI; Piotr PIETRAKOWSKI; Beata Zysiak-Christ (Communications of International Proceedings, 2020)
The relationship between stress and human functioning in an organization has been the subject of research all over the world for years. Most of the studies in this area are focused on medical and psychological aspects. In the era of the development of ICT support tools, it is possible to implement the thermoactive scanning instruments in the methodology of assessing the relationship of stress factors (stressors) with the distribution of selected neurotransmitters. A derivative of this type of research is the ability to assess management / command styles, which is extremely useful in assessing the suitability of employees for positions held in the organization.
Keywords: thermoactive scanning; IT in medicine; stress; motor activities